Knowledge of COVID-19 and Health Literacy among Patients Seeking Care in an Emergency Department - Barry, Connor; Green, Stephen; Payne, MD, Brian; Holmes, MD, Justin; Xu, MD PhD, K. Tom (International Journal of Innovative Research in Medical Science, 2021)
Background: As the US continues to experience increases of COVID-19 cases, there is an urgent need to identify ways to improve individuals’ knowledge of COVID-19 to achieve effective prevention and vaccination. The primary objective of the current study was to examine whether the knowledge of COVID-19 was associated with the general health literacy among patients in an emergency department. Methods: A sample of 252 adults was collected in an urban ED. Patients’ knowledge of COVID-19 was measured by the agreement to 10 statements. Health literacy was measured by the Brief Health Literacy Screen (BHLS). Participants were also asked about their primary source of COVID-19 information, sociodemographics, comorbidities and familiarity with the healthcare system at baseline. Bivariate and multivariate analyses were conducted. Results: The average COVID-19 knowledge score was 7.09 (range 0-10) and BHLS score, 11.09 (range 3-15). About 43% obtained the information primarily from TVs, radios, and newspapers and only 8% from scientific sources. The group with the primary source being social media had the lowest average COVID-19 knowledge score of 6.25. The BHLS and COVID-19 knowledge scores were positively correlated in both bivariate and multivariate analyses. Compared to primary source of information being social media, internet sites and searches (p=0.03) and families, relatives, and friends (p=0.02) were associated with higher COVID-19 knowledge scores, controlling for other factors. Education and income levels were statistically significant in both the bivariate and regressions. Conclusions: Patients with better general health literacy had better knowledge of COVID-19. To better prevent further increases in COVID-19 transmission and improve the rate of vaccination, individuals of low educational and income levels should be prioritized in community interventions. Regulations on and/or guard against misinformation presented on social media platforms should be included in any effective interventions to improve individuals’ knowledge of COVID-19.